1993
DOI: 10.1530/acta.0.1280289
|View full text |Cite
|
Sign up to set email alerts
|

Multihormonal response to CRH in a patient with Cushing syndrome and a pituitary adenoma producing ACTH and GH

Abstract: Preoperative bilateral and simultaneous catheterization of the inferior petrosal sinuses was performed in a patient with Cushing's syndrome. This procedure revealed parallel intersinus gradients for ACTH, PRL, GH and a response of all these hormones to CRH. The patient had transphenoidal surgery and a soft white-yellowish mass occupying the whole sella conditioned a total hypophysectomy. Morphologic studies and immunostaining techniques revealed a rare mixed pituitary adenoma of ACTH and GH containing cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, somatotroph adenomas showing hypersecretion of ACTH are extremely rare. There have been, to our knowledge, only five published reports of somatotroph adenomas accompanied by excessive ACTH secretion [2,5,8,21,24]. We also experienced a case of somatotroph adenoma with high serum GH, PRL, and ACTH levels.…”
Section: Introductionmentioning
confidence: 79%
“…However, somatotroph adenomas showing hypersecretion of ACTH are extremely rare. There have been, to our knowledge, only five published reports of somatotroph adenomas accompanied by excessive ACTH secretion [2,5,8,21,24]. We also experienced a case of somatotroph adenoma with high serum GH, PRL, and ACTH levels.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, it is unlikely that underestimation by immunohistochemical techniques might involve 18 of 22 tumours reported in the present study, that theoretically could have had a variable proportion of GH or PRL secreting cells within the adenoma. Indeed, it has been reported that oCRH can elicit in vitro increases in hormones other than ACTH in mixed ACTH and PRL and in mixed ACTH and GH secreting adenomas (Yamaji et al, 1985;Bughalho et al, 1993). In both cases the mechanism underlying this finding was unexplained.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it has been reported that oCRH can elicit in vitro increases in hormones other than ACTH in mixed ACTH and PRL and in mixed ACTH and GH secreting adenomas (Yamaji et al, 1985;Bughalho et al, 1993). Indeed, it has been reported that oCRH can elicit in vitro increases in hormones other than ACTH in mixed ACTH and PRL and in mixed ACTH and GH secreting adenomas (Yamaji et al, 1985;Bughalho et al, 1993).…”
Section: Discussionmentioning
confidence: 99%